Chemo-mechanical failure mechanisms of the silicon anode in solid-state batteries - Huo, Hanyu; Jiang, Ming; Bai, Yang; Ahmed, Shamail; Volz, Kerstin; Hartmann, Hannah; Henss, Anja; Singh, Chandra Veer; Raabe, Dierk; Janek, Jürgen; Justus Liebig University Giessen (My University, 2024)
Silicon is a promising anode material due to its high theoretical specific capacity, low lithiation potential and low lithium dendrite risk. Yet, the electrochemical performance of silicon anodes in solid-state batteries is still poor (for example, low actual specific capacity and fast capacity decay), hindering practical applications. Here the chemo-mechanical failure mechanisms of composite Si/Li6PS5Cl and solid-electrolyte-free silicon anodes are revealed by combining structural and chemical characterizations with theoretical simulations. The growth of the solid electrolyte interphase at the Si|Li6PS5Cl interface causes severe resistance increase in composite anodes, explaining their fast capacity decay. Solid-electrolyte-free silicon anodes show sufficient ionic and electronic conductivities, enabling a high specific capacity. However, microscale void formation during delithiation causes larger mechanical stress at the two-dimensional interfaces of these anodes than in composite anodes. Understanding these chemo-mechanical failure mechanisms of different anode architectures and the role of interphase formation helps to provide guidelines for the design of improved electrode materials.
Keywords: ddc:540